2020
DOI: 10.17648/sinergia-2236-7608-v24n1-9635
|View full text |Cite
|
Sign up to set email alerts
|

A Sucessão Familiar Em Pequenas Empresas

Abstract: A veia empreendedora do brasileiro já é conhecida e quando este obtém sucesso no seu empreendimento, o negócio até então individual, passa a envolver também sua família, englobando passado, presente e futuro, em prol da perpetuação do negócio familiar através do processo sucessório. O presente estudo objetivou compreender como se deu o processo de sucessão familiar vivenciado por empresas do ramo de prestação de serviços na cidade de Chapecó/SC. Caracteriza-se por um estudo de natureza aplicada, com abordagem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…In addition to leadership and credibility, the interviewee also shows concern about maintaining the status of their company's reputation. This is an aspect that can be related to the culture of the company of the participant of the study, which corroborates the sayings of Ricca and Saad (2012) and Zambarda and Vortmann (2020). It is observed the concern of the leader of the enterprise to maintain what had been achieved after the 15 years of operation of his organization.…”
Section: Responses From the Interviewed Ownersupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to leadership and credibility, the interviewee also shows concern about maintaining the status of their company's reputation. This is an aspect that can be related to the culture of the company of the participant of the study, which corroborates the sayings of Ricca and Saad (2012) and Zambarda and Vortmann (2020). It is observed the concern of the leader of the enterprise to maintain what had been achieved after the 15 years of operation of his organization.…”
Section: Responses From the Interviewed Ownersupporting
confidence: 88%
“…The theoretical reason has a contributory focus and aims to contribute to the enrichment of the state of the art related to the process of family succession. The national scientific literature already has theoretical and empirical studies that deal with this theme, as can be observed in Trancoso, Huber and Carvalho (2015), Zambarda and Vortmann (2020), França and Marchetti Filho (2019) and Volpato et al (2018).…”
Section: Uniting Knowledge Integrated Scientific Research For Global ...mentioning
confidence: 96%
“…Favorable aspects to family succession reveal the contribution of intra-family dynamics in the path of trust strengthened by bonds and affective ties, as well as values of the pro-business family institution culture, that is, with the recognition of skills, efficiency, dedication and loyalty (Lima, 2016;Zambarda & Vortmann, 2020;Brandt, Scheffer, & Gallon, 2020). In line with the entrepreneurial dream of the founder, a culture permeated by consensus around the growth and continuation of the business is perpetuated (Lodi, 1994), which imposes family relationships in which family and business culture are mixed (Frugis, 2007), in identities guided by credibility, leadership, charisma, and perseverance (Ricca, 2012).…”
Section: Succession In Family Businessesmentioning
confidence: 99%